Digital logistics, strategic cognitive readiness and employee training - Thomas Neukirchen; Matthias Klumpp (Artificial Intelligence and Digital Transformation in Supply Chain Management: Innovative Approaches for Supply Chains. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 27, 2019)
Purpose: We consider long-term structural implementation risks connected to digitalization in production and logistics. Similar to considerations regarding automation, we identify areas of potential corporate benefits and corresponding necessary adjustments in task descriptions and employee behavior. Methodology: Case study using an interactive process analysis and annotations method (interaction room) for a digitalization effort in a German power plant component company, including employees in digital developments early on. Survey of the concept of strategic cognitive analysis for logistics digitalization (systematic literature research). Findings: Analysis of the concept of strategic cognitive readiness is given for logistics digitalization and related to training requirements. This is connected to the presented case study which results in (i) augmented and digitalized process (ii) employee training requirements regarding strategic cognitive readiness. Originality: The concept of strategic cognitive readiness, originating from a military context, had been widely identified as a core variable with regards to successful automation prior to related widespread adoption. Nonetheless, recent research shows that measures aimed at effectively integrating employees, if taken, have fallen short in many cases.
urn:nbn:de:gbv:830-882.054134; 10419/209196; https://econpapers.repec.org/RePEc:zbw:hiclpr:27
Keywords: 650; Digitalization; Training; Cognitive readiness; Case study